Implication of hazard to consumer: case study in Petronas Sungai Udang, Melaka / Hariyantie Ali - Ali, Hariyantie (Faculty of Business and Management, 2009)
This study is to determine the implication of hazards to the consumers. The study will focus to the potential hazard occurred in heat exchanger cleaning and the implication of hazards itself to the consumer. Hazard can be defined as a situation that poses a level of threat to life, health, property, or environment. Hazard can be occurred everywhere to everybody. Same goes to implementing heat exchanger cleaning, there are some potential hazards that organization has to bear it and become the risk to organization. The potential hazards that maybe occurred while cleaning are people injury, property damaged, bundle drop, slippery working surface and so on. When the hazards become the risk to organization, it will effect to customer or client satisfaction. When the hazards become the risk to organization, it will effect to customer or client satisfaction. Customer satisfaction is seen as a key differentiator and increasingly has become a key element of business strategy. Therefore, customer will dissatisfy with the services provided by Science Tech Solution Sdn.Bhd if the hazard happened during the cleaning process. So research will be conducted to identify to identify the implication of hazard to the consumer.